2016
DOI: 10.1007/s00426-016-0762-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased cognitive demands boost the spatial interference effect in bimanual pointing

Abstract: It is beyond controversy that in bimanual coordination tasks, parameter planning related to the movements of one hand influences the planning and execution of movements simultaneously performed with the other hand. A well-researched example of such bimanual interference is the finding that reaction times tend to be longer when preparing bimanual pointing movements with different amplitudes than for equal amplitude movements. Interestingly, these reaction time costs were found to increase when movement targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…To determine reaction time (RT), we computed the resultant velocity of the positional data obtained from both infrared markers. Movement onset and offset were defined by a velocity threshold (all calculations identical to Stanciu et al, 2017). The moment the markers exceeded a velocity of 0.05 m/s was defined as movement onset and the moment their velocity dropped below 0.05 m/s, and their distance was less than 20 mm from the movement target, was defined as movement offset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine reaction time (RT), we computed the resultant velocity of the positional data obtained from both infrared markers. Movement onset and offset were defined by a velocity threshold (all calculations identical to Stanciu et al, 2017). The moment the markers exceeded a velocity of 0.05 m/s was defined as movement onset and the moment their velocity dropped below 0.05 m/s, and their distance was less than 20 mm from the movement target, was defined as movement offset.…”
Section: Discussionmentioning
confidence: 99%
“…The setup was identical to the one we have used and described previously (Stanciu et al, 2017). Participants sat in a dimly lit room in front of a monitor (19″ IPS monitor, Dell P1914S, 1280 × 1024 pixel, 30 cm × 37.5 cm, refresh rate 60 Hz) that was flatly screwed onto the table surface in vertical orientation (portrait mode).…”
Section: Setup and Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…They study phonological, phonetic, lexical, grammatical, semantic aspects of this phenomenon. Moreover, it was suggested that interference may be primarily related to cue translation and response selection processes rather than resulting from crosstalk [3].…”
Section: Research Questions and Methodsmentioning
confidence: 99%